HIERARCHIC STRUCTURE OF NASOPHARYNX MICROBIOTIC COMMUNITY IN PATIENTS WITH ACUTE RESPIRATORY INFECTION - Klymniuk, S.I.; Romaniuk, L.B.; Pokryshko, O.V.; Savchuk, M.M.; Tkachuk, N.I.; Tvorko, M.S.; Borak, V.P. (Інфекційні хвороби, 2015)
The results of the study of microbiota of nasal mucosa of patients with acute respiratory infections and acute upper respiratory tract pathology are presented. It is revealed that the microbe variety of the nose and nasopharynx forms associations of staphylococci, streptococci, Neisseria, Moraxella, hemophilic bacteria, sometimes Enterobacteriacea and Pseudomonadaceae, mostly of streptococci and staphylococci. Populations of organisms differ in their levels of colonization. The highest values were characteristic for streptococcal community – 7,88 lg CFU/ml.